Customer Perception of Online Food Delivery and Analysis of Factors Affecting Customers (Asian Business Research, 2022)
The online food delivery industry has great potential for development in China. As a new type of service industry, online food delivery has changed with time and China's economic development. Therefore, understanding young customer needs and requests requires constant updating. Only by better understanding the needs of customers can more targeted suggestions be provided for Chinese food delivery development. This study was conducted in the early stage of the COVID-19 outbreak in China, which represents a unique point in time. As the main group of online food delivery users, young people were selected as the survey subjects of this study. As described in this study, a binary logistic regression model is adopted to analyze factors that affect food delivery orders. Empirical studies have found that living expenses of 2001-4000 yuan, 4001-7000 yuan, and bad weather have a significant positive effect on purchasing behavior. Online food delivery users assign a high degree of emphasis on the taste of meals. These results suggest some strategies to attract Chinese online food delivery users: improving food safety supervision, maintaining the taste of meals, and increasing review system credibility.